Prediction and analysis of Tokyo Olympic Games swimming results: impact of the COVID-19 pandemic on swimmers' performance - Demarie, S.; Chirico, E.; Galvani, C. (International Journal of Environmental Research and Public Health, 2022)
Due to the COVID-19 pandemic in the 2019-2020 season, swimming competitions and training have been limited leading to a setback in performances. The study analyzed if, during the subsequent season, swimmers` have been able to regain the lost performance. Swimming time trends were analyzed comparing Tokyo with Rio Olympics and with mathematically predicted results. The gap between the gold medalist and the last finalist, and the differences between men and women have also been considered. Swimming competition results of females and males, in 100 m and 200 m Freestyle and Backstroke, were collected from the Olympics` official website. Results showed that at Tokyo Olympics almost all swimmers` times improved as compared to Rio`s. Analysis of performance trends highlighted that performance progression does not proceed in a linear fashion and that is best predicted by more recent results. Women`s progression was higher than men`s and the gap between the first and last finalist constantly decreased, except for the Tokyo Olympics. In conclusion, the unprecedented Tokyo Olympic Games and qualification year seems not to have disrupted all Olympic swimmers` performance, suggesting that stakeholders support and athlete`s coping ability might safeguard the subsistence of performance.